(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This work addresses theater in animated forms, more specifically the Lambe-Lambe Theatre, delving into the world of this recent language of animation. The research provides a brief historical contextualization of the antecedents of animation and optical devices. It also addresses the emergence of street photographers, the origin of the Lambe-Lambe Theatre, its 30 years of existence and its relationship with the street.